The effect of the imposition of fines for overdue books on third and fourth year students of some selected high schools in Manila - Ajayi, Nathaniel Akinola (1983)
The education program in a school is strengthened in direct proportion to the quality of the school library service, for the school library is the keystone of a quality educational program. The purpose of this study is to determine the effect of the imposition of fines for overdue books on high school students.